Association between type of cerebral palsy and the cognitive levels - Ratna Dewi Kusumaningrum; Elizabeth Siti Herini; Djauhar Ismail (Indonesian Pediatric Society, 2009)
Background Cerebral palsy is the main cause of physical disabilityduring childhood. Assessment is necessary to acknowledge thelevel of intelligence of the patients and to prevent impairmentsin order to plan the prompt intervention.Objectives To evaluate the cognitive levels of cerebral palsy andassociation between cognitive levels and its types.Methods We conducted a cross-sectional study on subjectsfrom Sekolah Luar Biasa Negeri 3 Yogyakarta. Intelligence wasmeasured using the Stanford-Binet intelligence scales, whereasdiagnosis of cerebral palsy was based on criteria of the AmericanAcademy for Cerebral Palsy (AACP). Data were analyzed usingchi-square test.Results There were 35 subjects, comprising of 21 boys and 14girls aged 5-18 years. The results show that in general, childrenwith cerebral palsy had mental retardation in several cognitivelevels. Children with hemiplegia type (1 subject) had IQ level that equals to mental retardation. Children with spastic diplegia type (6 subjects) showed borderline IQ (1) and mental retardation (5). Children with quadriplegia type ( 15 subjects) had superior IQ (1), borderline (7) and mental retardation (7). Out of 13 subjects with athetoid type 2, had borderline IQ (2), and mental retardation (11). The statistical analysis with chi-square test resulted in P = 0.114 (P < 0.05).Conclusion Our data showed that most patients with cerebral palsy had mental retardation of several cognitive level but there was no significant association between each type of cerebral palsy with cognitive levels.